RELEVANSI PANDANGAN GEREJA TENTANG POLITIK BAGI KARYA PASTORAL DI PAROKI KATEDRAL ST. MARIA PALANGKA RAYA - Hunayati, Hunayati (SEPAKAT-Jurnal Pastoral Kateketik, 2016)
This article explores how the Catholic Churchâs relevance about politics as thepastoral work especially to the Parish of Cathedral St. Maria Palangka Raya.The Catholic Church holds that the political participation of citizens is crucialfor the creation of policies that ensure the common good. Therefore, theefforts to introduce political and sustainable activities in relation to politicaleducation for the people need to be enhanced in order to realize that politics isalso the field of Church pastoral work.